Public Understanding and Institutional Strategies of Zakat on Oil Palm Plantations : A Case Study of Merangin Regency - Tirsa Guslia Nugroho; Rafidah; Addiarrahman (Lembaga Bale Literasi, 2025)
This study aims to determine the level of public understanding regarding zakat on oil palm plantations in Merangin Regency and to analyze the strategies implemented by the National Zakat Agency (BAZNAS) in improving such understanding. Employing a qualitative approach with inductive and descriptive analysis, this research focused on field facts obtained from observations, interviews, and documentation, involving oil palm farmers and BAZNAS administrators as subjects. The findings indicate that low awareness among farmers is influenced by attitudes, knowledge, and income, where many prefer to distribute zakat directly to relatives or the needy rather than through official institutions, while limited knowledge and incomes below the nisab threshold further reduce compliance. Moreover, 93.1% (27 out of 29) farmers demonstrated understanding only at the basic level of translation, which affects their awareness in fulfilling zakat obligations. To address this, BAZNAS has adopted outreach strategies, including lectures, sermons, Ramadan safari programs, brochure distribution, zakat transfer services, and promotional campaigns, aimed at strengthening literacy and institutional participation in zakat management.